Pemahaman Konsep Tasamuh (Toleransi) Siswa Dalam Ajaran Islam - Sholeh, Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
This article focuses on the understanding â€œtasamuhâ€ concept by theÂ students in the learning Islamic. This article is the result of researchÂ that using quantitative method, while to get the data using collectingÂ data technique: observation, questionnaire, and documentation. TheÂ result of this research shows that: First, variable of Qurâ€™an-Hadith lessonhas contribution to understanding â€œtasamuhâ€ concepts by the studentsÂ significantly. This is evidenced by the result of SPSS analysis for windowsÂ with significance level p= 0,042 and in the partial analysis the contributionÂ is 4,9%. Second, variable of Qurâ€™an-Hadith lesson has contribution toÂ understanding â€œtasamuhâ€ concepts by the students significantly. This isÂ evidenced by the result of SPSS analysis for windows with significanceÂ level p= 0,012 and in the partial analysis the contribution is 6,9%. Third,Â variable of Qurâ€™an-Hadith lesson do not have contribution to understandingÂ â€œtasamuhâ€ concept by the students significantly. This is evidenced by theÂ result of SPSS analysis for windows with significance level p= 0,469 andin the partial analysis the contribution is 0,7%. Fourth, based on theÂ result of double regression analysis use SPSS for window was obtainedÂ determinant coefficient R2= 0,117; p= 0,009. Its mean 12% variation ofÂ variable of understanding â€œtasamuhâ€ concept of the students influencedby Al-Qurâ€™an Hadith lesson, Aqidah Akhlak, and Fiqh at the same time.Â The rest are influenced by other variable beside the variable of Al-Qurâ€™anHadith, Aqidah Akhlak, and Fiqh.keywords: Understanding, Tasamuh, Contribution